Occurrence and distribution of microplastics in the surface water and sediment of two typical estuaries in Bohai Bay, China. Issue 7 (3rd June 2019) - Wu, Nan; Zhang, Ying; Zhang, Xiaohan; Zhao, Ze; He, Jiahui; Li, Wenpeng; Ma, Yongzheng; Niu, Zhiguang
Abstract : Estuaries are considered to be seriously polluted by microplastics. Abstract : Estuaries are considered to be seriously polluted by microplastics. As the most important water body in North China, the pollution level of microplastics in two typical estuaries (Haihe Estuary (HHE) and Yondingxinhe Estuary (YDXE)) of Bohai Bay is not well understood. The occurrence and distribution of microplastics in the surface water and sediment of HHE and YDXE were investigated. The mean concentration of microplastics in surface-water samples was 1485.7 ± 819.9 items per m 3 for HHE and 788.0 ± 464.2 items per m 3 for YDXE, respectively, whereas the concentration of microplastics in sediment was 216.1 ± 92.1 items per kg dw for HHE and 85.0 ± 40.1 items per kg dw for YDXE, respectively. The concentration of microplastics in surface-water and sediment-samples of HHE was higher than that of YDXE, though YDXE is a typical sewage-received river. Anthropogenic activities and the river input were the main sources of microplastic pollution in estuarine areas. Sewage rivers could be point sources of microplastic pollution on a small scale. The small size (particle diameter < 1 mm) of microplastics was a dominant feature, the most abundant shape was fiber and colored microplastics were found widely in YDXE and HHE. We provided detailed information on microplastic pollution to support their control and management in HHE and YDXE.